Histological and micro‐CT analysis of peri‐implant soft and hard tissue healing on implants with different healing abutments configurations. Issue 10 (23rd September 2018) - Souza, André Barbisan; Alshihri, AbdulMonem; Kämmerer, Peer W.; Araújo, Maurício G.; Gallucci, German O.
Abstract: Objective: The aim of this study was to assess the effect of different abutment configurations on peri‐implant soft and hard tissue healing. Materials and Methods: Two‐piece dental implants, 3.5 mm in diameter and 8 mm in length, were placed in four beagle dogs. Two different transmucosal healing abutment configurations were randomly selected: one with a wide emergence profile (WE) (45° angulation with implant long axis) and the other with a narrow emergence profile (NE) (15° angulation with implant long axis). After four months of healing, the animals were sacrificed. Micro‐CT scans were taken for mesio‐distal analysis; subsequently, the biopsies were prepared for bucco–lingual histometric analyses. Several measurements were taken using the following reference points: marginal mucosal level (MML), apical barrier epithelium (aBE), implant shoulder (IS), marginal bone crest (BC), and first bone‐to‐implant contact (fBIC). Results: In the micro‐CT analysis, the distance from IS‐fBIC was 1.11 ± 0.66 mm for WE and 0.12 ± 0.21 mm for NE ( p  = 0.004). The IS‐BC of WE was −0.54 ± 0.80 mm, whereas NE presented 0.76 ± 0.48 mm ( p  = 0.002). The histometric analysis showed that both groups presented comparable dimensions of peri‐implant biologic width ( p  > 0.05). However, in the distance from IS to BC, the WE showed a mean distance of −0.66 ± 0.78 mm while NE was 0.06 ± 0.42 mm ( p  = 0.039); the IS to fBIC was 0.89 ± 0.68 mm for WE while NE was 0.30 ± 0.30 mm ( p  = 0.041). Conclusion: The design of the transmucosal component can influence the establishment of the peri‐implant biologic width. The flat and wide emergence profile induced an apical displacement of the peri‐implant biologic width and more bone loss.